2019
DOI: 10.1111/jcmm.14065
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor‐α‐induced protein 8‐like 2 is a novel regulator of proliferation, migration, and invasion in human rectal adenocarcinoma cells

Abstract: Tumour necrosis factor‐α‐induced protein 8‐like 2 (TIPE2) is a tumour suppressor in many types of cancer. However, the mechanism of action of TIPE2 on the growth of rectal adenocarcinoma is unknown. Our results showed that the expression levels of TIPE2 in human rectal adenocarcinoma tissues were higher than those in adjacent non‐tumour tissues. Overexpression of TIPE2 reduced the proliferation, migration, and invasion of human rectal adenocarcinoma cells and down‐regulation of TIPE2 showed reverse effects. TI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…At room temperature, colonies were fixed with methanol for 15 min and subsequently stained with 0.5% crystal violet for 30 min. The plates were scanned and the numbers of colonies were counted [31].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…At room temperature, colonies were fixed with methanol for 15 min and subsequently stained with 0.5% crystal violet for 30 min. The plates were scanned and the numbers of colonies were counted [31].…”
Section: Methodsmentioning
confidence: 99%
“…Cells (1 × 10 4 /well) were suspended in the medium containing 0.6% agarose and overlaid onto a basal layer of 1.2% agarose in 6-well plates. After 14 days, colonies were observed under an Olympus CKX41 microscope and the numbers of colonies were counted [31].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…TIPE2 expression level in rectal cancer tissues was also much higher than that in adjacent normal tissues. TIPE2 suppressed proliferation, growth, migration, and invasion of rectal adenocarcinoma cells via inhibiting Wnt/β-catenin and TGF-β/Smad2/3 signaling pathways, indicating it might be a potential target in rectal adenocarcinoma treatment 75 ( Table 1 ). In the study of papillary thyroid carcinoma (PTC), TIPE2 overexpression was observed in tumor samples, and inhibited viability, proliferation, and invasion of PTC cells.…”
Section: Roles Of Tipe2 In Cancersmentioning
confidence: 99%